Costarica Mengual & Thompson, 2009 (Insecta: Diptera: Syrphidae) junior homonym of Costarica Kocak & Kemal, 2008 (Insecta: Orthoptera): proposed replacement by Tiquicia nom. nov. - Thompson, F. Christian (Zootaxa, 2012)
The name, Costarica Mengual and Thompson, 2009, was originally proposed for an endemic Costa Rican species, Allograpta zumbadoi Thompson, 2000 (Thompson et al. 2000). Unfortunately, this name was earlier used as a replacement name for Rowellia Carbonell, 2002, a grasshopper, by Kocak and Kemal (2008).